INVISIBLE WORKFORCE, INVISIBLE RIGHTS: AN ANALYTICAL STUDY OF WOMEN LABOUR IN RAJASTHAN’S UNORGANIZED SECTOR AND THE EFFICACY OF LABOUR WELFARE LAWS THROUGH A HUMAN RIGHTS LENS - Singh , Kavita; Anila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women constitute a significant proportion of the unorganized workforce in Rajasthan, engaging in sectors such as agriculture, construction, domestic work, and handicrafts. Despite their crucial economic contributions, they remain largely invisible in formal policy frameworks and are denied access to basic labour rights and social protections. This article examines the status of women workers in Rajasthan's unorganized sector, assesses the effectiveness of labour welfare legislation, and critically evaluates these legal frameworks through the lens of human rights.